2017
DOI: 10.1002/ece3.3055
|View full text |Cite
|
Sign up to set email alerts
|

Giant invasive Heracleum persicum: Friend or foe of plant diversity?

Abstract: The impact of invasion on diversity varies widely and remains elusive. Despite the considerable attempts to understand mechanisms of biological invasion, it is largely unknown whether some communities’ characteristics promote biological invasion, or whether some inherent characteristics of invaders enable them to invade other communities. Our aims were to assess the impact of one of the massive plant invaders of Scandinavia on vascular plant species diversity, disentangle attributes of invasible and noninvasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 89 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Therefore, our results suggest that anthropogenic dispersal may be a major factor contributing to the successful invasion of L. polyphyllus and H. sosnowskyi , together with their individual characteristics, which include environmental tolerance, high fertility, phenotypic plasticity, cold resistance, and the ability to occupy new biotopes. Both species have turned into transformers and supplanted the native species, significantly reducing the diversity of biogeocenoses [ 65 , 68 ]. Thus, these species require further study to successfully control their invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results suggest that anthropogenic dispersal may be a major factor contributing to the successful invasion of L. polyphyllus and H. sosnowskyi , together with their individual characteristics, which include environmental tolerance, high fertility, phenotypic plasticity, cold resistance, and the ability to occupy new biotopes. Both species have turned into transformers and supplanted the native species, significantly reducing the diversity of biogeocenoses [ 65 , 68 ]. Thus, these species require further study to successfully control their invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of studies have showed that plant invasions greatly reduce the biomass, coverage, evenness, richness and diversity of native plant species ( Flory and Clay, 2010 ; Yuguda et al., 2022 ), and plant invasions also could cause a significant increase in the litter biomass of invaded communities, which further benefits for excluding native plants ( Gooden and French, 2014 ). Additionally, plant communities containing only native species have a higher invasibility than those that included alien species, and alien plants that have similar functional traits with natives are more easily to enter and dominate the native plant communities ( Gooden and French, 2015 ; Li et al., 2015 ; Rijal et al., 2017 ). Moreover, environmental changes may affect the invasion process, e.g., seedling survival rate and drought tolerance of the invasive species Pennisetum ciliare are all increased by combinations of drought and warming, while this synergistic effect decreases leaf respiration of the native accompanying species Heteropogon contortus and causes substantial carbon loss, which accelerates native plant death ( Ravi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ecological significance of the Heracleum in terms of the negative effect on the local biodiversity has recently been reported in its invasive range in northern Europe [7]. Beside its significant impact on ecosystem, various species of the plant are used for variety of purposes which include as a fodder crop, ornamental use, food additives like spices, and in pharmaceutical applications [8,9].…”
Section: Introductionmentioning
confidence: 99%